2007
DOI: 10.1063/1.2803073
|View full text |Cite|
|
Sign up to set email alerts
|

Air-stable n-channel organic thin-film transistors with high field-effect mobility based on N,N′-bis(heptafluorobutyl)-3,4:9,10-perylene diimide

Abstract: The thin-film transistor characteristics of n-channel organic semiconductor, N,N′-bis(2,2,3,3,4,4,4-heptafluorobutyl)-perylene tetracarboxylic diimide, are described. The slip-stacked face-to-face molecular packing allows a very dense parallel arrangement of the molecules, leading to field-effect mobility as high as 0.72cm2V−1s−1. The mobility only slightly decreased after exposure to air and remained stable for more than 50days. Our results reveal that molecular packing effects such as close stacking of peryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
156
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(165 citation statements)
references
References 26 publications
6
156
3
Order By: Relevance
“…Since the effects of OH and water-based reactions are of particularly concern, we also prepared TCNQ single-crystal devices with highly water-repellent amorphous fluoropolymer gate dielectrics which do not possess OH groups [72,73]. The exhibited transistor characteristics were almost identical to those of the SiO 2 devices, indicating the minor effects of electron-trapping centers.…”
Section: Air-stable N-type Sc-ofets Of Tcnq and Ptcdamentioning
confidence: 99%
See 1 more Smart Citation
“…Since the effects of OH and water-based reactions are of particularly concern, we also prepared TCNQ single-crystal devices with highly water-repellent amorphous fluoropolymer gate dielectrics which do not possess OH groups [72,73]. The exhibited transistor characteristics were almost identical to those of the SiO 2 devices, indicating the minor effects of electron-trapping centers.…”
Section: Air-stable N-type Sc-ofets Of Tcnq and Ptcdamentioning
confidence: 99%
“…The result contrasts with the fact that the majority of organic transistors suffer from significant or fatal effects of deep electron traps, causing poor performance of the n-type transistors. As a result of tremendous effort in developing n-channel semiconductors, air-stable and high-mobility devices were reported recently [68,72,73]. However, reports on transistors with a V th less than 10 V are very rare and poorly reproducible.…”
Section: Air-stable N-type Sc-ofets Of Tcnq and Ptcdamentioning
confidence: 99%
“…N , NЈ-dialkyl-3,4,9,10-perylene tetracarboxylic diimide ͑PTCDI-Cn͒, especially, is very promising n-type materials with a high electron mobility, and studied intensively from the first stage of researches on OTFTs. [14][15][16][17][26][27][28][29][30][31][32][33][34][35][36][37][38][39] For example, Horowitz et al have reported the first n-type organic TFT made of N , NЈ-diphenyl PTCDI 14 yr ago. 26 After 6 yr, Malenfant et al have reported a N,NЈ-dioctyl PTCDI TFT with fairly high electron mobility as high as 0.6 cm 2 / V s. 27 Jones et al have synthesized corecyanated PTCDI with fluorinated alkyl chains, and reported an air-stable TFT with electron mobility of 0.64 cm 2 / V s. 28 Chesterfield et al have reported strikingly high electron mobility in N , NЈ-dioctyl PTCDI TFT of up to 1.7 cm 2 / V s through exquisite control of deposition condition, 29 and after that many research groups have poured their efforts to develop high-mobility n-type PTCDI OTFTs by modifying the molecular structure with core-substitution or with changing the substituent on the imide N atoms, by controlling deposition condition, by optimizing device structure such as the surface state of dielectrics and electrode contact, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The lower offcurrent in air is related to the oxidation of some doped PTCDI radical anions. 19 The air-stability of PyB-doped F-PTCDI-C4 TFTs was investigated by monitoring the performance of the devices stored in air as a function of time ͓Fig. 3͑c͔͒, without applying a continuous bias.…”
mentioning
confidence: 99%
“…17 Here we investigate the effects of n-type doping on the air-stability of vacuum-processed n-channel OTFTs by changing the doping location. Two n-channel semiconductors, namely, N , NЈ-dibutyl-1,7-difluoroperylene-3,4:9,10-tetracarboxylic diimide ͑F-PTCDI-C4͒ and N , NЈ-ditridecyl-perylene-3,4:9,10-tetracarboxylic diimide ͑PTCDI-C13͒, were chosen as the active materials for two reasons: ͑i͒ both exhibit excellent electron mobilities only under an inert atmosphere 16,19 and ͑ii͒ both have LUMO levels ͑Ϫ3.76 and Ϫ3.70 eV for F-PTCDI-C4 and PTCDI-C13, respectively͒ right above the empirical onset region ͑−3.8 to − 4.0 eV͒ observed for air-stability of arylene diimide-based n-channel OTFTs. 20 We employed a previously reported cationic dye, PyB, as the dopant because it is stable in air and commercially available.…”
mentioning
confidence: 99%